Saturn-Shaped Ice Burst Pattern and Fast Basal Binding of an Ice-Binding Protein from an Antarctic Bacterial Consortium - Kaleda, A; Haleva, L; Sarusi, G; Pinsky, T; Mangiagalli, M; Bar Dolev, M; Lotti, M; Nardini, M; Braslavsky, I (Langmuir, 2019)
Ice-binding proteins (IBPs) bind to ice crystals and control their growth, enabling host organisms to adapt to subzero temperatures. By binding to ice, IBPs can affect the shape and recrystallization of ice crystals. The shapes of ice crystals produced by IBPs vary and are partially due to which ice planes the IBPs are bound to. Previously, we have described a bacterial IBP found in the metagenome of the symbionts of Euplotes focardii ( EfcIBP). EfcIBP shows remarkable ice recrystallization inhibition activity. As recrystallization inhibition of IBPs and other materials are important to the cryopreservation of cells and tissues, we speculate that the EfcIBP can play a future role as an ice recrystallization inhibitor in cryopreservation applications. Here we show that EfcIBP results in a Saturn-shaped ice burst pattern, which may be due to the unique ice-plane affinity of the protein that we elucidated using the fluorescent-based ice-plane affinity analysis. EfcIBP binds to ice at a speed similar to that of other moderate IBPs (5 ± 2 mM-1 s-1); however, it is unique in that it binds to the basal and previously unobserved pyramidal near-basal planes, while other moderate IBPs typically bind to the prism and pyramidal planes and not basal or near-basal planes. These insights into EfcIBP allow a better understanding of the recrystallization inhibition for this unique protein